2021
DOI: 10.14710/jp.20.2.140-151
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Peer Rejection in Adolescent Internalizing Problems

Abstract: Emotional distress, such as symptoms of anxiety, depression, and withdrawal, is on the rise among teenagers today. These symptoms are generally grouped into internalizing problems. Based on research, a risk factor that contributes to internalizing problems is peer rejection. This study aims to determine the effect of peer rejection on adolescent internalizing problems. Research design is quantitative research with a multistage random sampling technique as a data collection technique. The subjects of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Besides this, Syakarofath et al have a similar conclusion on this perspective, that the research result and data analysis illustrate that negative peer issues have an influence on the teenager's internalizing [11]. Internalizing problems is a pervasive issue during adolescence, it needs to be handled well instead of developing further psychological problems.…”
Section: Peer Relationshipsmentioning
confidence: 63%
See 2 more Smart Citations
“…Besides this, Syakarofath et al have a similar conclusion on this perspective, that the research result and data analysis illustrate that negative peer issues have an influence on the teenager's internalizing [11]. Internalizing problems is a pervasive issue during adolescence, it needs to be handled well instead of developing further psychological problems.…”
Section: Peer Relationshipsmentioning
confidence: 63%
“…Lack of exercise and social interaction would definitely harm individuals' physical health. Analogous to Syakarofath et al's research, it advocates that social withdrawal has been closely linked to health problems such as cardiovascular disease, immune system problems, and early death [11]. Stemming from social withdrawal can lead to increased psychological stress, which in turn affects the function of the cardiovascular system and the proper functioning of the immune system.…”
Section: Physical Health Problemsmentioning
confidence: 90%
See 1 more Smart Citation
“…Peer problems that were most commonly identified among adolescents were difficulties or challenges in peer DOI 10.18502/kss.v9i5.15166 interactions and relationships. Peer problems can manifest in a variety of ways, including peer rejection, exclusion, and bullying by other kids [20,21,22,23,24,25]. A study from a Finnish middle school reported that 20% of 4447 students had experienced bullying by their peers [23].…”
Section: Discussionmentioning
confidence: 99%
“…Selanjutnya terdapat perbedaan efek pengalaman adverse childhood experience terhadap internalizing problem jika dianalisis berdasarkan gender. Pada perempuan kemunculan internalizing problem dianggap lebih tinggi dibandingkan dengan laki-laki sebagai strategi coping yang dianggap paling sesuai (Almuneef et al, 2017;Smith et al, 2016;Shopiani et al, 2021;Syakarofath et al, 2021).…”
Section: Prosedur Dan Analisis Dataunclassified